Voltage harmonic elimination with RLC based interface smoothing filter - Chandrasekaran K.; Ramachandaramurthy V.K. (Institute of Physics Publishing, 2023)
Active filters; Busbars; Electric inverters; Electric power factor correction; Engineering education; Videodisks; Voltage regulators; Digital simulation; Dynamic voltage restorer (DVR); Series active filters; Smoothing filters; Switching harmonics; Total harmonic distortion (THD); Voltage harmonics; Voltage source inverter; Harmonic analysis